Physiology of de parathyroid glands. Disfunction and functional parameters of paratyroid laboratory - Santiago-Peña, Luis Francisco (Revista ORL, 2019)
Calcium and Phosphorus are involved in important functions of the organism, both intracellular and extracellular. Therefore, there must be regulatory mechanisms that maintain calcium and phosphorus concentrations at their normal intervals. The objective of this article is to review the physiology of the parathyroid gland, as well as the role of vitamin D and Fibroblast Growth Factor 23 (FGF 23) in phosphocalcic metabolism and also interpret analytical alterations for the proper study of pathologies of phosphocalcium metabolism.